2016
DOI: 10.12688/f1000research.10225.2
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating phylogenies using k-mers: from trees to networks

Abstract: Ernst Haeckel based his landmark Tree of Life on the supposed ontogenic recapitulation of phylogeny, i.e. that successive embryonic stages during the development of an organism re-trace the morphological forms of its ancestors over the course of evolution. Much of this idea has since been discredited. Today, phylogenies are often based on families of molecular sequences. The standard approach starts with a multiple sequence alignment, in which the sequences are arranged relative to each other in a way that max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Computational simulations and empirical studies demonstrate that approaches based on k -mer count can support the scalable inference of phylogenies (Chan et al, 2014; Bernard et al, 2016a,b) and identify regions of lateral transfer within a dataset (Cong et al, 2016a,b). Parameters including k can be adjusted to minimize the effects of sequence divergence and genome rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Computational simulations and empirical studies demonstrate that approaches based on k -mer count can support the scalable inference of phylogenies (Chan et al, 2014; Bernard et al, 2016a,b) and identify regions of lateral transfer within a dataset (Cong et al, 2016a,b). Parameters including k can be adjusted to minimize the effects of sequence divergence and genome rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…# distance using 25-mers (see Methods). For each pair of genomes a and b we transformed $ %& into a similarity value ' %& and generated a similarity network, following our earlier approach 18 ; we consider this network to depict phylogenetic relatedness among these genomes, i.e. to be a phylogenomic network.…”
Section: Resultsmentioning
confidence: 99%
“…cliques, which reflect evolutionary events and dynamics of microbial genomes. For instance, we recovered the progressive separation of the different genomic lineages throughout their evolution 18 and showcased particular relationships between isolates not observed using a classical tree structure 7 .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In such cases, a non-tree-like network representation of genome evolution is more appropriate. Recent studies [60,61] have demonstrated the scalability and applicability of AF methods to quickly infer networks of relatedness among microbial genomes. Although we did not consider networks in this study, the curated benchmarking data sets can be easily extended to AF phylogenetic analysis beyond a tree-like structure in the future.…”
Section: Discussionmentioning
confidence: 99%